Multiproxy study reveals equality in the deposition of flaked lithic grave goods from the Baltic Stone Age cemetery Zvejnieki (Latvia) - Anđa Petrović; Jessica Bates; Aija Macāne; Ilga Zagorska; Mark Edmonds; Kerkko Nordqvist; Aimée Little (PLoS ONE, 2025)
The Stone Dead Project carried out analysis of the flaked lithic assemblages from burial contexts at Zvejnieki cemetery, Latvia. Zvejnieki (c. 7500−2500 cal. BC) represents one of the largest Stone Age burial grounds in Europe, consisting of over 330 burials containing 350 individuals. Using a multiproxy approach, combining geological, technological, functional, spatial and depositional context information, we compare the biographies of lithic grave goods with biographical information (age, sex) of the humans they accompany. Results show gender equality in lithic offerings whilst children are the age group most frequently given lithic grave goods. Certain typologies appear to have carried particular significance and were possibly made, and sometimes broken, as part of funerary rituals. The implications of these and other findings are discussed and placed within their broader archaeological context.